Effectiveness of topical sunscreen use to prevent skin cancers: systematic review - Sari, Luh Putu Venny Cempaka (International Journal of Research in Medical Sciences, 2021)
Topical sunscreen is a potential modality to prevent skin cancer development in vulnerable people although few study has evaluated its effectiveness in clinical setting. This study is aimed to review most recently available evidence on the clinical effectiveness of topical sunscreen in preventing skin cancers. We identified literature from online databases including Pubmed and Google Scholar and included population-based study evaluating the effect of sunscreen usage and risk of skin cancers, including melanoma, squamous cell carcinoma (SCC), and basal cell carcinoma (BCC) either as primary objective or as a confounder in multivariate analysis. Data form included articles was harvested and analyzed with thematic analysis. Final analysis included 11 articles. Of these, 6 reported results on melanoma, 4 reported on BCC, and 3 on SCC. Overall, there was conflicting evidence on the effectiveness of topical sunscreen in preventing skin cancer. Available evidence found that topical sunscreen was most effective in preventing melanoma and SCC. However, there was considerable heterogenicity in study design and definition of sunscreen treatment between included articles that may affect the results. There are no consensus among included articles, including among RCTs, on the ideal topical sunscreen regiment to prevent skin cancer. There are conflicting evidence on the clinical effectiveness of topical sunscreen to prevent skin cancer although evidence suggest that it would be effective in preventing melanoma and SCC. More clinical studies should be conducted with special emphasis on ensuring subject apply the sunscreen correctly and consistently.